Efficiency of Mobile Application of Thai Criteria Based Dispatch: A Randomized Controlled Crossover Trial - Jengsuebsant, Nantanan; Wittayachamnankul, Borwon; Tianwibool, Parinya; Tangsuwanaruk, Theerapon; Wongtanasarasin, Wachira; Sutham, Krongkarn (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The main purpose of the emergency medical system is a timely and appropriate response that significantly impacts health outcomes. In Thailand, due to lack of staff, emergency medical personnel at the dispatch center have to multitask to interview and dispatch the EMS responses. According to these problems the novel triage mobile application “Triagist” was developed based on Criteria Based Dispatch (CBD) to optimize prehospital care. This study is a pilot study aiming to test the app by evaluating the reliability and rapidity of code dispatching using “Triagist” compared with the usual method; ITEMS, Criteria Based Dispatch Handbook, or emergency medical personnel’ experiences only. A randomized-controlled crossover (AB/BA) design was conducted which compared mobile application “Triagist” and conventional methods. Eighteen experienced emergency medical personnel each were randomly assigned to AB or BA arm. The primary outcome measure was the accuracy and rapidity of code dispatching to 6 simulated scenarios among experienced emergency medical personnel. Using triage mobile application by experienced emergency medical personnel had gained a chance of correct dispatch 1.5 times, which was significantly more accurate than the conventional method (95%CI 1.03-2.28) and also significantly more rapid dispatch than the conventional method (82 vs 95 sec., p = 0.03)